Impact of cholesterol homeostasis within cochlear cells on auditory development and hearing loss - Wu, Jichang; Ji, Peilin; Zhang, Andi; Hu, Haixia; Shen, Yilin; Wang, Quan; Fan, Cui; Chen, Kaili; Ding, Rui; Huang, Weiyi; Xiang, Mingliang; Ye, Bin (Frontiers in Cellular Neuroscience, 2024)
Cholesterol is the most abundant sterol molecule in mammalian cells, which not only constitutes the cell membrane but also plays essential roles in the synthesis of important hormones, synapse formation, and cell signal transduction. The effect of hypercholesterolemia on hearing has been studied extensively, and multiple studies have demonstrated that hypercholesterolemia is a risk factor for hearing loss. However, the impact of cholesterol homeostasis within auditory cells on peripheral auditory development and maintenance has not been evaluated in detail. Mutations in certain cholesterol metabolism-related genes, such as NPC1, SERAC1, DHCR7, and OSBPL2, as well as derivatives of cholesterol metabolism-related ototoxic drugs, such as βcyclodextrin, can lead to disruptions of cholesterol homeostasis within auditory cells, resulting in hearing loss. This article aims to review the impact of cholesterol homeostasis within auditory cells on the peripheral auditory function from the following two perspectives: 1. changes in cholesterol homeostasis regulatory genes in various hearing loss models; 2. mechanisms underlying the effects of some drugs that have a therapeutic effect on hearing loss via regulating cholesterol homeostasis. This article aims to summarize and analyze the impact of disruption of cellular cholesterol homeostasis within auditory cells on hearing, in order to provide evidence regarding the underlying mechanisms.